Anode and secondary battary
The negative electrode for secondary batteries, featuring isotropically treated natural graphite and artificial graphite layers, addresses adhesion and expansion issues by reducing electrolyte reactions and enhancing adhesion, leading to improved performance and rapid charging capabilities.
Patent Information
- Application Number
- KR1020230133971
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-10-14
- Filing Date
- 2023-10-10
- Publication Date
- 2026-11-05
- Estimated Expiration
- 2043-10-10
AI Technical Summary
Existing secondary batteries face challenges in achieving improved adhesion and expansion performance, as certain additives can enhance one aspect of performance but deteriorate others, necessitating research on material selection and combination to optimize battery characteristics.
A negative electrode for secondary batteries is designed with a first layer of isotropically treated natural graphite and a second layer of artificial graphite, comprising secondary and single particles, to enhance adhesion and expansion performance by reducing electrolyte reactions and maximizing the adhesion of the cathode active material layer.
The use of isotropically treated natural graphite and artificial graphite in the cathode active material layers improves electrode expansion performance and adhesion, resulting in enhanced rapid charging effects and stability.
Abstract
Description
Technology Field
[0001] This application claims the benefit of the filing date of Patent Application No. 10-2022-0132407 filed with the Korean Intellectual Property Office on October 14, 2022, the entire contents of which are incorporated herein.
[0002] The present invention relates to a negative electrode for a secondary battery and a secondary battery including the same. Background Technology
[0003] Secondary batteries are widely applied not only to portable devices but also to electric vehicles (EVs) and hybrid electric vehicles (HEVs) powered by electric driving sources.
[0004] These secondary batteries are attracting attention as a new energy source for improving eco-friendliness and energy efficiency, as they not only have the primary advantage of being able to drastically reduce the use of fossil fuels but also the advantage of not generating any by-products from the use of energy.
[0005] Generally, a secondary battery includes a positive electrode, a negative electrode, a separator interposed between the positive and negative electrodes, and an electrolyte. Additionally, electrodes such as the positive and negative electrodes may have an electrode active material layer provided on a current collector.
[0006] As the utilization of secondary batteries increases, diverse battery performance characteristics are required. Attempts have been made to introduce additives into the active material layer to improve battery performance; however, depending on the type of additive, while some aspects of battery performance may be improved, others may actually deteriorate. Accordingly, research is needed on the selection or combination of materials included in the electrode to improve the required performance of secondary batteries. The problem to be solved
[0007] The present invention aims to provide a negative electrode for a secondary battery with improved adhesion and expansion performance, and a secondary battery including the same. means of solving the problem
[0008] One embodiment of the present invention is
[0009] The whole house;
[0010] A first negative active material layer provided on the above current collector; and
[0011] It includes a second cathode active material layer provided on the first cathode active material layer, and
[0012] The first cathode active material layer comprises natural graphite treated with isotropic pressure, and
[0013] The above second negative electrode active material layer comprises artificial graphite in the form of secondary particles and artificial graphite in the form of single particles, thereby providing a negative electrode for a secondary battery.
[0014] Another embodiment of the present invention provides a secondary battery comprising a negative electrode, a positive electrode, and a separator for the secondary battery.
[0015] Another embodiment of the present invention is the step of forming a first negative active material layer on a current collector;
[0016] The method includes the step of forming a second cathode active material layer on the first cathode active material layer.
[0017] The first cathode active material layer is isotropically treated natural graphite or BET with a specific surface area of 1 m² 2 / g to 3 m 2 Contains natural graphite in / g,
[0018] A method for manufacturing a negative electrode for a secondary battery is provided, wherein the second negative electrode active material layer comprises artificial graphite in the form of secondary particles and artificial graphite in the form of single particles. Effects of the invention
[0019] The cathode of the present invention utilizes isotropically treated natural graphite and single-particle artificial graphite along with artificial graphite in the form of secondary particles in the cathode active material layer. This results in relatively lower orientation within the electrode and reduced adverse reactions with the electrolyte, thereby improving the expansion performance of the electrode. Furthermore, by forming isotropically treated natural graphite at the bottom of the cathode active material layer, the adhesion of the cathode active material layer is maximized, enabling an improved rapid charging effect. Specific details for implementing the invention
[0020] Hereinafter, the present invention will be described in more detail to aid in understanding the invention. The present invention may be embodied in various different forms and is not limited to the embodiments described herein. In this case, terms or words used in this specification and claims should not be interpreted as being limited to their ordinary or dictionary meanings, but should be interpreted in a meaning and concept consistent with the technical spirit of the present invention, based on the principle that the inventor can appropriately define the concept of the terms to best describe his invention.
[0021] In this specification, terms such as “comprising,” “comprising,” or “having” are intended to specify the existence of the implemented features, numbers, steps, components, or combinations thereof, and should not be understood as precluding the existence or addition of one or more other features, numbers, steps, components, or combinations thereof.
[0022] Furthermore, when it is said that a part, such as a layer, is "above" or "on" another part, this includes not only the case where it is "directly above" the other part, but also the case where there is another part in between. Conversely, when it is said that a part is "directly above" another part, it means that there is no other part in between. Also, saying that a part is "above" or "on" a reference part means that it is located above or below the reference part, and it does not necessarily mean that it is located "above" or "on" facing the opposite direction of gravity.
[0023] In this specification, the particle size refers to the average particle size indicated by D50. D50 can be defined as the particle size at the 50% reference of the particle size distribution and can be measured using a laser diffraction method. For example, a method for measuring the average particle size (D50) of the cathode active material can be performed by dispersing the particles of the cathode active material in a dispersion medium, introducing them into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000), irradiating them with ultrasound of approximately 28 kHz at an output of 60 W, and then calculating the average particle size (D50) corresponding to 50% of the volume accumulated in the measuring device.
[0024] In this specification, the description referred to only as "active material layer" without the expressions of the first and second may be applied to both the first and second active material layers.
[0025] A negative electrode for a secondary battery according to one embodiment of the present specification comprises a current collector; a first negative active material layer provided on the current collector; and a second negative active material layer provided on the first negative active material layer, wherein the first negative active material layer comprises natural graphite treated with isotropic pressure, and the second negative active material layer comprises artificial graphite in the form of secondary particles and artificial graphite in the form of single particles. In other words, the negative electrode for a secondary battery comprises two layers of negative active material layers, and also includes artificial graphite in the form of secondary particles, natural graphite treated with isotropic pressure, and artificial graphite in the form of single particles, and by placing the natural graphite treated with isotropic pressure at the bottom of the negative active material layer, a negative electrode with excellent expansion performance and adhesion can be obtained.
[0026] A method for manufacturing a negative electrode for a secondary battery according to another embodiment comprises the steps of: forming a first negative electrode active material layer on a current collector; and forming a second negative electrode active material layer on the first negative electrode active material layer, wherein the first negative electrode active material layer is isotropically treated natural graphite or has a BET specific surface area of 1 m² 2 / g to 3 m 2 It includes natural graphite in g / g, and the second cathode active material layer includes artificial graphite in the form of secondary particles and artificial graphite in the form of single particles.
[0027] In this specification, "single particle" is a concept contrasted with a secondary particle form formed by the aggregation of tens to hundreds of primary particles, and means composed of 10 or fewer primary particles. Specifically, in the present invention, a single particle may be a single particle composed of one primary particle, or it may be a particle form formed by the aggregation of several primary particles.
[0028] In this specification, "primary particle" refers to the smallest unit of particle recognized when observing an active material through a scanning electron microscope, and "secondary particle" refers to a secondary structure formed by the aggregation of tens to hundreds of primary particles.
[0029] In this specification, "particle" refers to a grain of micro-scale, which, when magnified and observed, can be distinguished as "grains" having a crystalline form of tens of nanometers. Further magnification reveals distinct regions in which atoms form a lattice structure in a specific direction, which are referred to as "crystalliums." The particle size observed in XRD is defined as the crystal grain size. The crystal grain size can be quantitatively determined using the Scherrer equation based on XRD data.
[0030] According to one embodiment of the present invention, the first cathode active material layer comprises natural graphite treated with isostatic pressure. The natural graphite treated with isostatic pressure can be obtained through methods such as a Cold Isostatic Press (CIP). Specifically, spherical aggregate particles of controlled size obtained through an air-flow grinder are filled into a molding mold of a cold isostatic molding device, and after filling the four sides of the molding mold with water, cold isostatic molding is performed for 100 seconds at a molding pressure of 90 MPa. Subsequently, the spherical aggregate particles formed with cold isostatic pressure are crushed. Natural graphite treated with isostatic pressure can be obtained by mixing 100 parts by weight of the crushed spherical aggregate particles with 5 parts by weight of pitch (solid pitch), which is a carbon coating material, and carbonizing the mixture at a temperature of 1,250°C for 24 hours to obtain carbon coating, but the method for manufacturing natural graphite treated with isostatic pressure is not limited to the above description.
[0031] As described above, when using methods such as the Cold Isostatic Press (CIP) to obtain isostatically treated natural graphite, isostatic pressure can be applied to the raw material particles from all directions; therefore, there is an advantage that the internal voids of the raw material particles within the spherical aggregate particles are reduced and the specific surface area is decreased.
[0032] According to one embodiment of the present invention, as the first cathode active material layer comprises natural graphite treated with isotropic pressure, the orientation within the electrode is relatively lowered and side reactions with the electrolyte are reduced, thereby improving the expansion performance of the electrode and increasing the adhesion of the cathode active material layer.
[0033] According to one embodiment of the present invention, the BET specific surface area of the natural graphite is 1 m² 2 / g to 3 m 2 It can be / g. By using natural graphite having a BET specific surface area within the above range, there is an advantage in that the durability of the cell is improved. Specifically, 3 m 2 If it exceeds / g, durability decreases due to electrolyte side reactions, and 1 m 2 Cases below / g are difficult to implement and hinder electrolyte penetration. For example, 1.2 m 2 / g to 2.8 m 2 It can be / g and 1.2 m 2 / g to 2.8 m 2 It can be / g and 1.2 m 2 / g to 2.6 m 2 It can be / g, and 1.4 m 2 / g to 2.4 m 2 / g can be.
[0034] In this specification, the BET specific surface area can be measured by the BET (Brunauer-Emmett-Teller) measurement method using the BELSORP (BET equipment) of BEL JAPAN, for example, using an adsorbed gas such as nitrogen.
[0035] According to one embodiment of the present invention, the average particle size (D50) of the isotropically treated natural graphite may be 6 μm to 9 μm, 7 μm to 9 μm, or 8 μm to 9 μm. By using isotropically treated natural graphite having an average particle size (D50) within the above range, the effects of including isotropically treated natural graphite in the negative electrode active material layer (improvement of electrode expansion performance, increase in adhesion of the negative electrode active material layer) can be maximized.
[0036] The average particle size (D50) of the above isotropically treated natural graphite can be controlled through a process of grinding using an air-stream grinder. Specifically, flake-like graphite with an average particle size (D50) of 200 μm can be prepared and ground to control its size using an air-stream grinder, and the ground flake-like graphite can be subjected to a spheroidization process to obtain spherical aggregate particles, but the method of obtaining natural graphite with isotropically treated and controlled average particle size is not limited to the above description.
[0037] According to one embodiment of the present invention, the second cathode active material layer comprises artificial graphite in the form of secondary particles and artificial graphite in the form of single particles.
[0038] According to one embodiment of the present invention, the average particle size (D50) of the single-particle artificial graphite may be 6 μm to 9 μm, 7 μm to 9 μm, or 8 μm to 9 μm.
[0039] According to one embodiment of the present invention, the average particle size (D50) of the artificial graphite in the form of secondary particles may be 16 μm to 22 μm.
[0040] In one embodiment of the present invention, in order to obtain artificial graphite in the form of single particles having an average particle size (D50) of the above range and artificial graphite in the form of single particles, methods such as grinding using a jet mill and heat treating after grinding may be used. Specifically, needle coke may be ground using a jet mill and then sieved to obtain a powder with controlled size. Additionally, the powder may be heat-treated (graphitized) at 3,000°C for 20 hours under an inert argon (Ar) gas atmosphere to produce primary artificial graphite particles (or single particles), and after adding a binder such as petroleum-based pitch to the primary artificial graphite particles (single particles), the mixture may be heat-treated at 1,000°C or higher for 10 hours to obtain secondary artificial graphite particles in which the primary artificial graphite particles are aggregated.
[0041] In one embodiment of the present invention, the OI (004 / 110) of the single-particle artificial graphite is 35 or less, 25 or less.
[0042] The OI (004 / 110) of the second cathode active material layer above is a value obtained through X-ray diffraction analysis, and can be obtained using a general method of X-ray diffraction analysis, such as JIS K 0131-1996. The OI value of the cathode can be expressed as C004 / C110, where C004 represents the characteristic diffraction peak region of the (004) crystal plane and C110 represents the characteristic diffraction peak region of the (110) crystal plane.
[0043] The OI (004 / 110) of the single-particle artificial graphite of the second cathode active material layer is a value obtained through X-ray diffraction analysis, and can be obtained using a general method of X-ray diffraction analysis, such as using a Bruker D4 Endeavor X-ray diffraction analyzer. Additionally, the OI value of the cathode can be expressed as I004 / I110, where I004 represents the characteristic diffraction peak region of the (004) crystal plane and I110 represents the characteristic diffraction peak region of the (110) crystal plane.
[0044] These characteristics indicate the degree of orientation of the graphite crystals within the second negative electrode active material layer. A higher OI value indicates higher graphite orientation, while a lower OI value indicates lower orientation. When the orientation of the graphite crystals is low, the expansion position of the battery during charging expands randomly rather than in a specific direction, thereby improving the battery's expansion performance.
[0045] According to one embodiment of the present invention, the adhesion force of the first cathode active material layer to the current collector is 18 gF / cm or more. Since the cathode of the present invention is formed such that the first cathode active material layer and the current collector are in contact, the adhesion force of the isotropically treated natural graphite, which is the material of the first cathode active material layer, affects the adhesion force of the first cathode active material layer to the current collector.
[0046] According to one embodiment of the present invention, the adhesive strength of the isotropically treated natural graphite included in the first cathode active material layer is 18 gF / cm or more. The adhesive strength of the isotropically treated natural graphite can be adjusted according to the particle size distribution value.
[0047] In one embodiment of the present invention, the second negative electrode active material layer may include 30 to 90 parts by weight of the artificial graphite in the form of secondary particles based on 100 parts by weight of the negative electrode active material. Satisfying the above range has advantages in improving the expansion performance and energy density of the battery.
[0048] In one embodiment of the present invention, the second negative electrode active material layer may include 10 to 30 parts by weight of the single-particle artificial graphite based on 100 parts by weight of the negative electrode active material. Satisfying the above range has advantages in improving the expansion performance and energy density of the battery.
[0049] According to one embodiment of the present specification, each of the above negative electrode active material layers (the first negative electrode active material layer and the second negative electrode active material layer) may further include a negative electrode active material other than the above-described isotropically treated natural graphite, artificial graphite in the form of secondary particles, and artificial graphite in the form of single particles, and the types thereof are not limited.
[0050] In one embodiment of the present specification, the negative electrode active material in 100 parts by weight of each negative electrode active material layer may be included in an amount of 80 parts by weight or more and 99.9 parts by weight or less, preferably 90 parts by weight or more and 99.9 parts by weight or less, more preferably 95 parts by weight or more and 99.9 parts by weight or less, and even more preferably 98 parts by weight or more and 99.9 parts by weight or less.
[0051] According to additional embodiments of the present specification, the first cathode active material layer may further include a cathode binder in addition to isotropically treated natural graphite, and the second cathode active material layer may further include a cathode binder in addition to artificial graphite in the form of secondary particles and artificial graphite in the form of single particles.
[0052] The above-mentioned cathode binder can serve to improve adhesion between cathode active material particles and adhesion between the cathode active material particles and the cathode current collector. The above-mentioned cathode binder may be any known in the art, and non-limiting examples may include at least one selected from the group consisting of polyvinylidenefluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidenefluoride, polyacrylonitrile, polymethylmethacrylate, polyvinyl alcohol, carboxymethylcellulose (CMC), starch, hydroxypropylcellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and materials in which hydrogens thereof are substituted with Li, Na, or Ca, etc., and may also include various copolymers thereof.
[0053] The above-mentioned cathode binder may be included in an amount of 0.1 parts by weight or more and 20 parts by weight or less based on 100 parts by weight of the cathode active material layer, for example, preferably 0.3 parts by weight or more and 20 parts by weight or less, more preferably 0.5 parts by weight or more and 10 parts by weight or less.
[0054] The above-mentioned negative electrode active material layer may not include a conductive material, but may additionally include a conductive material if necessary. The conductive material included in the above-mentioned negative electrode active material layer is not particularly limited as long as it is conductive without causing chemical changes in the battery, and for example, graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, ketjen black, channel black, Farnes black, lamp black, thermal black; conductive fibers such as carbon fibers or metal fibers; conductive tubes such as carbon nanotubes; metal powders such as fluorocarbon, aluminum, or nickel powder; conductive whiskers such as zinc oxide or potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives may be used. The content of the conductive material in the above-mentioned negative electrode active material layer may be 0.01 to 20 parts by weight, preferably 0.03 to 18 parts by weight, relative to 100 parts by weight of the negative electrode active material layer.
[0055] The above negative electrode active material layer may further include a thickener such as Na-CMC (Sodium carboxymethyl cellulose), Li-CMC (Carboxymethyl cellulose lithium), or CNF (Cellulose nanofiber).
[0056] In one embodiment of the present specification, the thickness of the first and second negative electrode active material layers may each be 5 μm or more and 500 μm or less.
[0057] According to one embodiment of the present specification, the thickness ratio of the first and second negative electrode active material layers (thickness of the first negative electrode active material layer:thickness of the second negative electrode active material layer) may be 3:7 to 5:5.
[0058] In one embodiment of the present specification, the negative current collector may be conductive without causing chemical changes in the battery, and is not particularly limited. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. may be used as the current collector. Specifically, transition metals that adsorb carbon well, such as copper and nickel, may be used as the current collector. The thickness of the current collector may be 1 μm to 500 μm, but the thickness of the current collector is not limited thereto.
[0059] Further embodiments of the present specification provide a secondary battery comprising a negative electrode, a positive electrode, and a separator according to the embodiments described above.
[0060] In one embodiment of the present specification, the positive electrode comprises a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector and comprising the positive electrode active material. The thickness of the positive electrode active material layer may be 20 μm or more and 500 μm or less.
[0061] The above positive current collector is not particularly limited as long as it is conductive without causing chemical changes in the battery, and for example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface treated with carbon, nickel, titanium, silver, etc. may be used. In addition, the above positive current collector may typically have a thickness of 1 to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesion of the positive active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0062] In one embodiment of the present specification, the anode may include a lithium composite transition metal compound comprising nickel (Ni) and cobalt (Co) as an active material. The lithium composite transition metal compound may further include at least one of manganese and aluminum. The lithium composite transition metal compound may include 80 mol% or more, for example, 80 mol% or more and less than 100 mol% of nickel among the metals excluding lithium.
[0063] In one embodiment, the positive active material in 100 parts by weight of the positive active material layer may be included in an amount of 80 parts by weight or more and 99.9 parts by weight or less, preferably 90 parts by weight or more and 99.9 parts by weight or less, more preferably 95 parts by weight or more and 99.9 parts by weight or less, and even more preferably 98 parts by weight or more and 99.9 parts by weight or less.
[0064] According to additional embodiments of the present specification, the positive active material layer according to the above embodiments may further include a positive binder and a conductive material.
[0065] The anode binder described above can serve to improve adhesion between anode active material particles and adhesion between anode active material particles and anode current collector. The anode binder may be one known in the art, and non-limiting examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethylcellulose (CMC), starch, hydroxypropylcellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene butadiene rubber (SBR), fluororubber, or various copolymers thereof, and one of these alone or a mixture of two or more may be used.
[0066] The anode binder may be included in an amount of 0.1 parts by weight or more and 50 parts by weight or less based on 100 parts by weight of the anode active material layer, for example, preferably 0.3 parts by weight or more and 35 parts by weight or less, more preferably 0.5 parts by weight or more and 20 parts by weight or less.
[0067] The conductive material included in the above-mentioned positive electrode active material layer is used to impart conductivity to the electrode, and can be used without special restrictions as long as it has electronic conductivity without causing chemical changes within the battery. Specific examples include graphite such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber such as copper, nickel, aluminum, or silver; conductive whiskey such as zinc oxide or potassium titanate; conductive metal oxide such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and one of these alone or a mixture of two or more of these may be used.
[0068] Specifically, in one embodiment, the conductive material may include one or more of single-walled carbon nanotubes (SWCNT) and multi-walled carbon nanotubes (MWCNT). The conductive material may be included in an amount of 0.1 parts by weight or more and 2 parts by weight or less based on 100 parts by weight of the composition for the cathode active material layer, for example, preferably 0.3 parts by weight or more and 1.5 parts by weight or less, more preferably 0.5 parts by weight or more and 1.2 parts by weight or less.
[0069] The above-described anode and cathode may be manufactured according to conventional methods for manufacturing anodes and cathodes, except for using the above-described anode and cathode active materials. Specifically, they may be manufactured by applying a composition for forming an active material layer, comprising the above-described active material and optionally a binder and a conductive material, onto a current collector, followed by drying and rolling. At this time, the types and contents of the anode and cathode active materials, binder, and conductive material are as described above.
[0070] The above composition for forming the active material layer may further include a solvent. Specifically, the solvent may be a solvent generally used in the relevant technical field, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and one of these alone or a mixture of two or more may be used. The amount of solvent used is sufficient to dissolve or disperse the active material, conductive material, and binder, taking into account the coating thickness of the slurry and the manufacturing yield, and to have a viscosity that provides excellent thickness uniformity when coated for the manufacture of the anode and cathode. Alternatively, the anode and cathode may be manufactured by casting the above composition for forming the active material layer onto a separate support, and then laminating the film obtained by peeling it off from the support onto a current collector.
[0071] Further embodiments of this specification provide a method for manufacturing a negative electrode for a secondary battery according to the aforementioned embodiments.
[0072] The above manufacturing method comprises the step of forming a first negative active material layer on a current collector;
[0073] A method for manufacturing a negative electrode for a secondary battery, comprising the step of forming a second negative electrode active material layer on the first negative electrode active material layer,
[0074] The first cathode active material layer is isotropically treated natural graphite or BET with a specific surface area of 1 m²2 / g to 3 m 2 Contains natural graphite in / g,
[0075] The second cathode active material layer may include artificial graphite in the form of secondary particles and artificial graphite in the form of single particles.
[0076] A secondary battery according to one embodiment of the present invention comprises an assembly including a positive electrode, a negative electrode, a separator, and an electrolyte, and may be a lithium secondary battery.
[0077] The above separator separates the negative electrode and the positive electrode and provides a pathway for the movement of lithium ions. Any separator typically used as a separator in a secondary battery can be used without special limitations, and it is particularly desirable that it has low resistance to the movement of electrolyte ions and excellent electrolyte wettability. Specifically, a porous polymer film, such as a porous polymer film made of a polyolefin-based polymer like ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer, and ethylene / methacrylate copolymer, or a laminated structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, such as a nonwoven fabric made of high-melting-point glass fiber or polyethylene terephthalate fiber, may be used. Furthermore, a coated separator containing ceramic components or polymer materials may be used to ensure heat resistance or mechanical strength, and it may optionally be used in a single-layer or multi-layer structure.
[0078] Examples of the above electrolytes that can be used in the manufacture of lithium secondary batteries include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, molten inorganic electrolytes, etc., but are not limited to these.
[0079] Specifically, the electrolyte may include a non-aqueous organic solvent and a metal salt.
[0080] As the above-mentioned non-aqueous organic solvent, for example, aprotic organic solvents such as N-methyl-2-pyrrolidinone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, gamma-butyl lactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyl tetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolone, formamide, dimethylformamide, dioxolone, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphate triester, trimethoxymethane, dioxolone derivative, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivative, tetrahydrofuran derivative, ether, methyl propionate, ethyl propionate, etc. may be used.
[0081] In particular, among the above carbonate-based organic solvents, ethylene carbonate and propylene carbonate, which are cyclic carbonates, are high-viscosity organic solvents with high dielectric constants that effectively dissociate lithium salts, so they can be used preferably. Furthermore, if low-viscosity, low-dielectric constant linear carbonates such as dimethyl carbonate and diethyl carbonate are mixed with these cyclic carbonates in appropriate proportions, an electrolyte with high electrical conductivity can be produced, making it even more preferable to use.
[0082] The metal salt mentioned above may be a lithium salt, and the lithium salt is a substance that dissolves well in the non-aqueous electrolyte; for example, as the anion of the lithium salt, F - , Cl - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 -, CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - and (CF3CF2SO2)2N - One or more types selected from the group consisting of can be used.
[0083] In addition to the above electrolyte components, the above electrolyte may further include one or more additives for the purpose of improving the lifespan characteristics of the battery, suppressing the decrease in battery capacity, and improving the discharge capacity of the battery, such as, for example, a haloalkylene carbonate-based compound such as difluoroethylene carbonate, pyridine, triethylphosphite, triethanolamine, cyclic ether, ethylene diamine, n-glyme, triamide hexaphosphate, nitrobenzene derivative, sulfur, quinone imine dye, N-substituted oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol, or aluminum trichloride.
[0084] Further embodiments of the present invention provide a battery module comprising the aforementioned secondary battery as a unit cell and a battery pack comprising the same. Since the battery module and the battery pack include the secondary battery having high capacity, high rate capability and cycle capability, they can be used as a power source for medium-to-large devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles and power storage systems.
[0085] Since the secondary battery according to the embodiments of the present invention stably exhibits excellent discharge capacity, output characteristics, and cycle performance, it can be used as a power source for portable devices such as mobile phones, laptop computers, and digital cameras, as well as for medium-to-large devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems. For example, the battery module or battery pack can be used as a power source for one or more medium-to-large devices, including a power tool; an electric vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV); or a power storage system.
[0087] Hereinafter, preferred embodiments are presented to aid in understanding the present invention; however, the above embodiments are merely illustrative of the description, and it is obvious to those skilled in the art that various changes and modifications are possible within the scope and spirit of the description, and that such variations and modifications fall within the scope of the appended claims.
[0089] Example 1
[0090] A first cathode slurry was prepared by weighing natural graphite (adhesion strength: 19 gF / cm) with an average particle size (D50) of 9 μm and treated isotropically at a pressure of 80 MPa, SBR as a binder, CMC as a thickener, and carbon black as a conductive material in a weight ratio of 96:1:2:1 (natural graphite:SBR:CMC:carbon black), adding distilled water, and mixing. Next, a second cathode slurry was prepared by weighing artificial graphite in the form of secondary particles with an average particle size (D50) of 18 μm as a cathode active material, artificial graphite in the form of single particles with an average particle size (D50) of 8.5 μm (OI(004 / 110): 25), SBR as a binder, CMC as a thickener, and carbon black as a conductive material in a weight ratio of 95:1:3:1 (artificial graphite (secondary particle artificial graphite:single particle artificial graphite = 80:20):SBR:CMC:carbon black), adding distilled water, and mixing. A first cathode active material layer was formed by coating the prepared first cathode slurry onto a copper foil electrode current collector, and a second cathode active material layer was formed by coating the prepared second cathode slurry onto the surface of the first cathode active material layer to manufacture a cathode. At this time, the weight ratio of natural graphite included in the first cathode active material layer and artificial graphite included in the second cathode active material layer (natural graphite:artificial graphite) corresponds to 30:70, and the weight ratio of the artificial graphite in the form of secondary particles and the artificial graphite in the form of single particles (secondary particles: single particles) corresponds to 80:20.
[0092] Example 2
[0093] A cathode was prepared in the same manner as in Example 1, except that isotropically treated natural graphite with an average particle size (D50) of 9 μm and an adhesive strength of 22 gF / cm was used.
[0095] Example 3
[0096] The cathode was prepared in the same manner as in Example 1, except that natural graphite treated with isotropic pressure at 90 MPa was used.
[0098] Example 4
[0099] A cathode was prepared in the same manner as in Example 1, except that a mixture ratio of secondary particle artificial graphite and single particle artificial graphite was used as the cathode active material of the second cathode slurry at 70:30.
[0101] Comparative Example 1
[0102] A cathode was manufactured in the same manner as in Example 1, except that only a cathode active material layer containing artificial graphite in the form of secondary particles with a particle size (D50) of 18 μm was formed as the cathode active material layer.
[0104] Comparative Example 2
[0105] A cathode was manufactured in the same manner as in Example 1, except that a single layer of cathode active material was formed containing (mixed) artificial graphite in the form of secondary particles with a particle size (D50) of 18 μm and artificial graphite in the form of single particles with a particle size (D50) of 18 μm.
[0107] Comparative Example 3
[0108] A cathode was manufactured in the same manner as in Example 1, except that a single layer of cathode active material was formed containing (mixed) artificial graphite in the form of secondary particles with a particle size (D50) of 18 μm and natural graphite that has not been treated with isotropic pressure with a particle size (D50) of 9 μm.
[0110] Comparative Example 4
[0111] A cathode was manufactured in the same manner as in Example 1, except that a first cathode active material layer comprising natural graphite that has not been treated with isotropic pressure and has a particle size (D50) of 9 μm, and a second cathode active material layer comprising artificial graphite in the form of secondary particles and has a particle size (D50) of 18 μm were formed as the cathode active material layer.
[0113] Comparative Example 5
[0114] A cathode was manufactured in the same manner as in Example 1, except that a single layer of cathode active material was formed, comprising (mixed) isotropically treated natural graphite with a particle size (D50) of 9 μm, artificial graphite in the form of secondary particles with a particle size (D50) of 18 μm, and artificial graphite in the form of single particles with a particle size (D50) of 9 μm.
[0116] Comparative Example 6
[0117] A cathode was manufactured in the same manner as in Example 1, except that a single layer of cathode active material was formed, comprising (mixing) artificial graphite in the form of secondary particles with a particle size (D50) of 18 μm and artificial graphite in the form of single particles with a particle size (D50) of 9 μm.
[0119] Comparative Example 7
[0120] The cathode was manufactured in the same manner as in Example 1, except that a second cathode slurry was surface-coated on the copper foil electrode current collector above to form a second cathode active material layer, and a first cathode slurry was coated on the surface of the second cathode active material layer to form a first cathode active material layer.
[0122] The adhesion force between the negative electrode active material layer and the current collector of the manufactured negative electrode and the cycle expansion performance of the battery manufactured using the negative electrodes manufactured in the above examples and comparative examples were measured and are shown in Table 1 below.
[0124] (1) Method for measuring the adhesion strength (gF / cm) of the cathode active material layer: Each cathode prepared in the example and comparative example was rolled, dried in a vacuum oven at 130°C for 8 hours, then cut into a certain size, fixed to the center of a slide glass using tape, and then the peel strength was measured by peeling off the cathode current collector using a Universal Testing Machine (UTM).
[0125] (2) Cycle expansion performance (Swelling ratio(%)@30 thMethod for measuring cycle(charge): LiCoO2 as the positive electrode active material, Li-435 (manufactured by Denka) as the conductive material, a binder, and a thickener were mixed in a weight ratio of 96:2:2 (positive electrode active material:conductive material:binder+thickener), and an N-methylpyrrolidone (NMP) solvent was added to prepare a positive electrode slurry. The positive electrode slurry was coated onto aluminum foil, vacuum dried at approximately 130°C for 8 hours, and rolled to obtain an area of 1.7671 cm². 2 A positive electrode was manufactured. At this time, the positive electrode loading was ~3.4 mAh / cm² 2 A full-cell secondary battery was manufactured to the extent that it was prepared as follows. A polyethylene separator was interposed between the negative electrode prepared in the example and comparative example and the positive electrode prepared above, and then an electrolyte was injected to manufacture a full-cell secondary battery applying the respective negative electrode of the example and comparative example. The electrolyte used was prepared by adding vinylene carbonate (VC) at 0.5 wt% relative to the solvent to a non-aqueous electrolyte solvent in which ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 1:4, and dissolving LiPF6 at 1 M. The coin full-cell battery was charged and discharged with a charge range of SOC 0 to SOC 95, with the first cycle at 0.1 C, the second cycle at 0.2 C, and the third to the 30th cycle at 0.5 C. Subsequently, the swelling ratio was measured by the following Equation 1.
[0126] [Mathematical Formula 1]
[0127] Swelling ratio (%) = {(t2-t1) / t1} x 100
[0128] (The above t1 is the thickness of the negative electrode for the secondary battery before performing the first charge-discharge cycle, and the above t2 is the thickness of the negative electrode for the secondary battery after performing the 30th charge-discharge cycle)
[0129] cathode Adhesion of the negative electrode active material layer (gF / cm) Swelling ratio(%)@30 th cycle(Charge) BET specific surface area (m²) of natural graphite in the first cathode active material layer 2 / g) Example 1 19 18 2.14 Example 2 22 18 2.12 Example 3 21 17 2.02 Example 4 20 17 2.14 Comparative Example 1 14 21 - Comparative Example 2 15 23 - Comparative Example 3 14 24 3.2 Comparative Example 4 16 21 3.2 Comparative Example 5 16 20 2.14 Comparative Example 6 15 20 - Comparative Example 7 15 21 2.14
[0130] As shown in Table 1 above, it was confirmed that the adhesion strength of the negative electrode active material layer and the cycle expansion performance of the battery in Examples 1 to 4 were superior to the adhesion strength of the negative electrode active material layer and the cycle expansion performance of the battery in Comparative Examples 1 to 7.
Claims
Claim 1 A negative electrode for a secondary battery comprising: a current collector; a first negative active material layer provided on the current collector; and a second negative active material layer provided on the first negative active material layer, wherein the first negative active material layer comprises natural graphite treated with isotropic pressure, the second negative active material layer comprises artificial graphite in the form of secondary particles and artificial graphite in the form of single particles, wherein the second negative active material layer comprises 70 to 90 parts by weight of the artificial graphite in the form of secondary particles based on 100 parts by weight of the negative active material, and the second negative active material layer comprises 10 to 30 parts by weight of the artificial graphite in the form of single particles based on 100 parts by weight of the negative active material. Claim 2 In claim 1, the BET specific surface area of the natural graphite is 1 m² 2 / g to 3 m 2 Negative electrode for a secondary battery that is / g. Claim 3 A negative electrode for a secondary battery according to claim 1, wherein the average particle size (D50) of the natural graphite is 6 μm to 9 μm. Claim 4 A negative electrode for a secondary battery according to claim 1, wherein the average particle size (D50) of the single-particle artificial graphite is 6 μm to 9 μm. Claim 5 A negative electrode for a secondary battery according to claim 1, wherein the OI (004 / 110) of the single-particle artificial graphite is 35 or less. Claim 6 A negative electrode for a secondary battery according to claim 1, wherein the adhesion force of the first negative active material layer to the current collector is 18 gF / cm or more. Claim 7 delete Claim 8 delete Claim 9 delete Claim 10 A secondary battery comprising a negative electrode, a positive electrode, and a separator according to any one of claims 1 to 6. Claim 11 A method for manufacturing a negative electrode for a secondary battery, comprising the steps of: forming a first negative active material layer on a current collector; and forming a second negative active material layer on the first negative active material layer, wherein the first negative active material layer comprises natural graphite treated with isotropic pressure, the second negative active material layer comprises artificial graphite in the form of secondary particles and artificial graphite in the form of single particles, the second negative active material layer comprises 70 to 90 parts by weight of the artificial graphite in the form of secondary particles based on 100 parts by weight of the negative active material, and the second negative active material layer comprises 10 to 30 parts by weight of the artificial graphite in the form of single particles based on 100 parts by weight of the negative active material. Claim 12 In claim 11, the BET specific surface area of the natural graphite is 1 m² 2 / g to 3 m 2 A method for manufacturing a negative electrode for a secondary battery that is / g.
Citation Information
Patent Citations
Negative electrode for lithium secondary battery, and lithium secondary battery comprising the same
KR1020180124659A
Negative electrode and secondary battery comprising the negative electorde
KR1020220006006A
Graphite secondary particles and lithium secondary battery comprising thereof
KR1020160014539A
Negative electrode, and lithium secondarty battery comprising the negative electrode
KR1020190090497A
Negative electrode and lithium secondary battery comprising the negative electrode
KR1020200088237A
